The Immunomodulatory mechanism and research progress of mesenchymal stem cells in the treatment of allergic rhinitis - Yu-Meng Ye; Yu-Xin Zhao; Li-Rong Xiang; Chen-Yu Zou; Hao Xiao; Huan Lu; Hui Yang; Juan-Juan Hu; Hui-Qi Xie (Stem Cell Research & Therapy)
Abstract Background Allergic rhinitis (AR) affects 10–40% of the global population, yet current therapies (drugs, immunotherapy) face limitations in efficacy and safety. Mesenchymal stem cells (MSCs) have emerged as a promising alternative due to their immunomodulatory properties. Key Findings Preclinical studies demonstrate that MSCs from adipose, bone marrow, umbilical cord, and tonsils reduce AR symptoms (sneezing, nasal inflammation) and serum IgE (Immunoglobulin E) levels by restoring Th1/Th2 immune equilibrium and enhancing Treg (Regulatory T cells) activity. MSC-derived exosomes and hydrogel-encapsulated formulations further improve targeting and safety. However, clinical translation is hindered by heterogeneous protocols and unresolved long-term risks (e.g., tumorigenicity). Clinical Significance MSC-based therapies offer potential for durable AR remission by addressing immune dysregulation at its root. Future efforts must prioritize standardized production, phase I safety trials, and combination strategies (e.g., exosomes + hydrogels) to accelerate clinical adoption.